Brief Report: HIV Assisted Partner Services Among Those With and Without a History of Intimate Partner Violence in Kenya. (1st May 2018) - Goyette, Marielle S.; Mutiti, Peter M.; Bukusi, David; Wamuti, Beatrice M.; Otieno, Felix A.; Cherutich, Peter; Golden, Matthew R.; Spiegel, Hans; Richardson, Barbra A.; Ng'ang'a, Anne; Farquhar, Carey
Abstract : Background: HIV assisted partner services (APS) are a notification and testing strategy for sex partners of HIV-infected index patients. This cluster-randomized controlled trial secondary data analysis investigated whether history of intimate partner violence (IPV) modified APS effectiveness and risk of relationship dissolution. Setting: Eighteen HIV testing and counseling sites in Kenya randomized to provide immediate APS (intervention) or APS delayed for 6 weeks (control). Methods: History of IPV was ascertained at study enrollment and defined as reporting ever experiencing physical or sexual IPV. Those reporting IPV in the month before enrollment were excluded. We tested whether history of IPV modified intervention effectiveness and risk of relationship dissolution using population-averaged Poisson and log-binomial generalized estimating equation models. Exploratory analyses investigated associations between history of IPV and events that occurred after HIV diagnosis using log-binomial generalized estimating equation models. Results: The study enrolled 1119 index participants and 1286 partners. Among index participants, 81 (7%) had history of IPV. History of IPV did not modify APS effectiveness in testing, newly diagnosing, or linking partners to care. History of IPV did not modify the association between receiving immediate APS and relationship dissolution during the study. Conclusions: Among participants who had not experienced IPV in the last month but had experienced IPV in their lifetimes, our results suggest that APS is an effective and safe partner notification strategy in Kenya. As APS is scaled up in different contexts, these data support including those reporting past IPV and closely monitoring adverse events.